2003
DOI: 10.1101/gad.244103
|View full text |Cite
|
Sign up to set email alerts
|

TheArabidopsis SRR1gene mediates phyB signaling and is required for normal circadian clock function

Abstract: Plants possess several photoreceptors to sense the light environment. In Arabidopsis cryptochromes and phytochromes play roles in photomorphogenesis and in the light input pathways that synchronize the circadian clock with the external world. We have identified SRR1 (sensitivity to red light reduced), a gene that plays an important role in phytochrome B (phyB)-mediated light signaling. The recessive srr1 null allele and phyB mutants display a number of similar phenotypes indicating that SRR1 is required for no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
105
0

Year Published

2004
2004
2007
2007

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(108 citation statements)
references
References 74 publications
3
105
0
Order By: Relevance
“…This is in agreement with observations made during large-scale analyses of protein localization (Huh et al 2003). A similar subcellular localisation was reported for SRR1-GFP in Arabidopsis (Staiger et al 2003). However, no enrichment of the signal was seen on microtubules or at kinetochores.…”
Section: Conwrmation Of the Involvement Of Ber1 In Kinetochore Functionsupporting
confidence: 92%
See 3 more Smart Citations
“…This is in agreement with observations made during large-scale analyses of protein localization (Huh et al 2003). A similar subcellular localisation was reported for SRR1-GFP in Arabidopsis (Staiger et al 2003). However, no enrichment of the signal was seen on microtubules or at kinetochores.…”
Section: Conwrmation Of the Involvement Of Ber1 In Kinetochore Functionsupporting
confidence: 92%
“…Future experiments will address this hypothesis biochemically and hopefully identify the targets of Ber1p activity. Such experiments may allow us to shed light on the biochemical function of other members of the SRR1 family, in particular Arabidopsis SRR1 for which genetic studies have shown that it is involved in light perception and circadian rhythms (Staiger et al 2003). Proteasome subunits are heavily N-acetylated (Csank et al 2002) and the proteasome is very important for light perception and circadian rhythms in Arabidopsis (Hellmann and Estelle 2002;Mas 2005).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The sensitivity to red light reduced 1 (srr1) mutant (SRR1, GenBank Accession number NM125348) shows a de-etiolation phenotype that is weaker and a leaf rhythm phenotype that is stronger than that of the phyB mutant [21]. One possibility is that SRR1 is involved in two different but connected molecular functions, one in light signalling and the other in circadian rhythms.…”
Section: Multiplicity Of Pathwaysmentioning
confidence: 99%